THE ROLE AND IMPACT OF NEOLOGISMS IN MODERN ENGLISH LANGUAGE - Buxalicha Turgunova; Diyora Rustamova (TADQIQOTLAR, 2025)
ABSTRACT     This thesis examines the nature, classification, and sociocultural significance of neologisms in modern English. A neologism is generally defined as “ a new word or expression,  or  a  new  meaning  for  an  existing  word”.  The  study  explores  how neologisms emerge, the linguistic processes by which they are formed, and their role in reflecting and influencing contemporary culture. Drawing on the works of prominent linguists – including David Crystal, Jean Aitchison, and Steven Pinker – the research outlines  theoretical  perspectives  on  language  change  and  lexical  innovation.  The findings highlight that English is a dynamic, living language: hundreds of new words enter common usage each year, driven by technological advances, social change, and creative  word  formation  processes.  This  work  also  discusses  how  new  words  gain acceptance  or  fall  into  obscurity,  illustrating  both  the  rapid  adoption  of  useful neologisms  and  the  ephemeral  nature  of  others.  The  conclusion  emphasizes  that neologisms  are  both  products  and  agents  of  sociocultural  evolution,  serving  as  a barometer of change in modern English.